2016
DOI: 10.1021/acs.jced.5b01000
|View full text |Cite
|
Sign up to set email alerts
|

Density, Speed of Sound, Refractive Index, and Viscosity of the Binary Mixtures of N,N-dimethylacetamide with Methanol and Ethanol

Abstract: The thermophysical behavior of the binary mixtures N,Ndimethylacetamide + methanol and N,N-dimethylacetamide + ethanol has been studied through the measurement of density, ρ, speed of sound, u, refractive index, n D , and kinematic viscosity, ν, over the entire mole fraction range at the temperatures of 283.15, 298.15 and 313.15 K and at p = 99.0 kPa. Excess volumes, V E , excess isentropic compressibilities,κ S E , refractive index deviations, Δn D , and viscosity deviations, Δη, were also calculated and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Further it is observed that ΔnD values decrease when temperature increases for both systems, which suggests that the light propagates faster. Based on our previous results [11], it can be seen that mixtures containing lower alkanols give more positive ΔnD values than those containing higher chain alkanols.…”
Section: Refractive Index Deviationmentioning
confidence: 67%
See 1 more Smart Citation
“…Further it is observed that ΔnD values decrease when temperature increases for both systems, which suggests that the light propagates faster. Based on our previous results [11], it can be seen that mixtures containing lower alkanols give more positive ΔnD values than those containing higher chain alkanols.…”
Section: Refractive Index Deviationmentioning
confidence: 67%
“…Obviously, all these factors are responsible of final balance between positive and negative contributions. The comparison of excess molar volumes of the binary systems containing higher chain alkanols with lower alkanols taken from our previous results [11], shows less negative V E values. According to several authors [37,38], the higher alkanols possess less proton-donating ability than the lower ones, and therefore heteroassociation effects are smaller in their mixtures, and V E values tend to shift towards positive values.…”
Section: The Plots Of V E Vs Mole Fraction X1 For the Binary Mixturementioning
confidence: 74%
“…The comparison of excess molar volumes of the binary systems containing higher chain alkanols with lower alkanols taken from our previous results [11], shows less negative V E values. According to several authors [37,38], the higher alkanols possess less proton-donating ability than the lower ones, and therefore heteroassociation effects are smaller in their mixtures, and V E values tend to shift towards positive values.…”
Section: Methodsmentioning
confidence: 74%
“…Ritzoulis and Fidantsi [5] reported refractive indices at T = 298. 15 Based on our previous results [11], it can be seen that mixtures containing lower alkanols give more positive ΔnD values than those containing higher chain alkanols.…”
Section: Refractive Index Deviationmentioning
confidence: 83%
See 1 more Smart Citation